Challenges to Realizing the Convention on the Rights of Persons with Disabilities (CRPD) in Australia for People with Intellectual Disability and Behaviours of Concern. Issue 2 (3rd March 2016) - Chan, Jeffrey
Abstract : It has been a significant period of time since Australia ratified the United Nations' Convention on the Rights of Persons with Disabilities 2006 (CRPD). While the CRPD brings significant positive changes in legislation, public policy, and service delivery (for example, in the National Disability Insurance Scheme), there are still a number of challenges in implementing the CRPD in Australia, particularly for people with intellectual disability who exhibit behaviours of concern. Some of the challenges include a negative perception of disability, the misrepresentation of occupational health and safety frameworks, and a revival of the call for congregate care living. Given these barriers to full CRPD realization, some of the solutions may include a closer engagement with families, other legislative frameworks, and industrial relations, and a stronger monitoring role for the CRPD implementation in Australia.